RESTORATION OF HISTORIC BUILDINGS IN ZANZIBAR - Makunza, John K. (Tanzania Journal of Engineering and Technology, 2018)
Looking at current state of most repaired historic buildings in Stone Town of Zanzibar, it is quite clear that the repair attempts made have not been very successful. Modern materials and techniques introduced in the repair works have often proven to be incompatible with the original materials causing accelerated deterioration of buildings fabric. This shows that, there is no comprehensive study undertaken so far on identifying the appropriate materials and restoration techniques. To solve this problem, a study has been made with the main objective of developing the means of restoring historic buildings by using materials existing in Stone Town of Zanzibar. The study was conducted through visual investigation and laboratory testing of materials taken from existing historical buildings and those that are currently being used for repair. Laboratory test conducted includes chemical analysis, grading, compressive strength and water absorption. The results showed some similarities in both materials, however, the combination ratios are not the same resulting into different properties. It has therefore been established that sand of the same grading pattern as the one found in the historic building mortar must be sought and utilized in making repair mortar at a ratio of 1 part lime to 3 parts sand. Keywords: Historic building, lime, limestone, coral stones and mortar